Solar cell module and preparation method thereof
By designing a composite electron transport layer in a perovskite trans-structure device, including a light scattering layer, a first electron transport layer and a second electron transport layer, the energy loss problem caused by the interface defects between the perovskite and the electron transport layer is solved, the electron transport efficiency and stability are significantly improved, and the device efficiency with excellent performance is achieved.
Patent Information
- Application Number
- CN202411833109.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-28
AI Technical Summary
In perovskite trans-structure devices, there are a large number of defects in the interface between the perovskite and the electron transport layer, resulting in serious energy loss and restricting efficiency improvement.
A composite electron transport layer is designed, including a light scattering layer, a first electron transport layer and a second electron transport layer. The light scattering layer increases light scattering and improves the light absorption of perovskites; the first electron transport layer fills the gaps of the light scattering layer to reduce surface roughness; the first and second electron transport layers with conduction band spread accelerate electron transport and reduce carrier recombination.
Effectively passivate the interface defects between the perovskite and the electron transport layer, reduce energy losses, significantly improve electron transport efficiency and stability, and thus obtain excellent device efficiency.
Smart Images

Figure CN119730547A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photovoltaics, and in particular relates to a solar cell assembly and a preparation method thereof. Background Art
[0002] In recent years, with the continuous deepening of research, perovskite batteries have made rapid progress, with the efficiency increasing from the initial 3.8% to more than 25%, and are hailed as "the new hope in the photovoltaic field."
[0003] Common perovskite cells can be divided into formal structure and trans structure according to their structure. The formal structure generally includes a stacked transparent conductive substrate, an electron transport layer, a perovskite absorption layer, a hole transport layer and a metal electrode. The commonly used material for the hole transport layer is Spiro-OMeTAD, which has poor thermal stability and is not conducive to industrial development. The trans structure generally includes a stacked transparent conductive substrate, a hole transport layer, a perovskite absorption layer, an electron transport layer and a metal electrode. This structure has a wider application prospect due to its excellent performance in photoelectric performance and thermal stability. However, there is a significant difference in the photoelectric conversion efficiency between the formal perovskite device and the trans device. The formal device started earlier in the development of perovskite and its efficiency is much higher than the trans device which started later.
[0004] For inverse devices, there are a large number of defects at the interface between the perovskite and the electron transport layer, which leads to serious energy loss and restricts efficiency improvement.
[0005] Therefore, how to passivate interface defects and further improve the electron transport efficiency and stability of the electron transport layer to obtain device efficiency with excellent performance is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the deficiencies of the prior art, the object of the present invention is to provide a solar cell module and a method for preparing the same. In the composite electron transport layer designed by the present invention, the light scattering layer can increase light scattering, improve the absorption of light by perovskite, and improve the short-circuit current of the device. The first electron transport layer can not only fill the gaps formed by the agglomeration of nanoparticles in the light scattering layer and reduce the surface roughness, but also the first electron transport layer and the second electron transport layer with a conduction band price difference can accelerate electron transport and reduce carrier recombination. The three layers cooperate with each other to effectively passivate the interface defects between the perovskite and the electron transport layer and reduce energy loss, thereby significantly improving the electron transport efficiency and stability of the composite electron transport layer, thereby obtaining the device efficiency with excellent performance, and having good development prospects.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a solar cell module having a composite electron transport layer, wherein the composite electron transport layer comprises a light scattering layer, a first electron transport layer and a second electron transport layer arranged in a stacked manner:
[0009] The light scattering layer is used to absorb the first light and form scattering; the first electron transport layer is used to transport electrons and fill the gaps in the light scattering layer; and there is a conduction band difference between the first electron transport layer and the second electron transport layer.
[0010] In the composite electron transport layer designed by the present invention, the light scattering layer can increase light scattering, improve the light absorption of perovskite, and improve the short-circuit current of the device. The first electron transport layer can not only fill the gaps formed by the agglomeration of nanoparticles in the light scattering layer and reduce the surface roughness, but also the first electron transport layer and the second electron transport layer with a conduction band price difference can accelerate electron transport and reduce carrier recombination. The three electron transport layers cooperate with each other to effectively passivate the interface defects between the perovskite and the electron transport layer and reduce energy loss, thereby significantly improving the electron transport efficiency and stability of the composite electron transport layer, thereby obtaining the device efficiency with excellent performance, and having good development prospects.
[0011] It should be noted that the conduction band price difference in the present invention refers to the difference in the bottom energy of the conduction band between the first electron transport layer and the second electron transport layer. In semiconductor physics, the conduction band is an energy region where electrons can move freely, and the energy position at its bottom plays a key role in the electrical properties of the material, especially the transmission of electrons and related physical processes. The size and positive and negative of this difference determine many electrical properties such as the tendency of electron transmission between the two materials. From the perspective of electron transmission, the conduction band price difference determines the direction of electron transfer and also affects the mobility of electrons near the interface of the two materials; from the perspective of the battery, the conduction band price difference can make the photogenerated electrons and holes move in different electrode directions, respectively, reducing the probability of electron-hole recombination, thereby improving the photoelectric conversion efficiency of the battery.
[0012] It should be noted that the light scattering layer has a wide band gap and is very thin, so electrons can directly tunnel through it. It should be noted that the first light refers to the sunlight irradiated onto the surface of the light scattering layer.
[0013] Preferably, the LUMO energy level of the first electron transport layer is greater than the LUMO energy level of the second electron transport layer.
[0014] Preferably, the material of the light scattering layer includes nano-oxide particles.
[0015] Preferably, the nano oxide particles include aluminum oxide and / or silicon oxide.
[0016] Preferably, the material of the light scattering layer further includes a nitrogen-containing heterocyclic compound.
[0017] In the present invention, the introduction of nitrogen-containing heterocyclic compounds into the light scattering layer helps to increase the electron transport rate of the composite electron transport layer.
[0018] Preferably, the nitrogen-containing heterocyclic compound includes 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole.
[0019] Preferably, the thickness of the light scattering layer is 1-10 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, etc., preferably 5-10 nm.
[0020] In the present invention, if the light scattering layer is too thin, it will not play the role of light scattering; if the light scattering layer is too thick, it will affect the electron transmission due to poor conductivity.
[0021] Preferably, the material of the first electron transport layer includes a fullerene derivative.
[0022] Preferably, the fullerene derivatives include [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) and / or indene-C 60 Bisadduct (ICBA).
[0023] Preferably, the material of the second electron transport layer includes C 60 .
[0024] Preferably, the thickness of the first electron transport layer is 1-10 nm, for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, etc., preferably 5-10 nm.
[0025] In the present invention, if the first electron transport layer is too thin, it will not fill the gaps in the light scattering layer, alleviate the unevenness of the upper surface, and reduce the surface roughness; if the first electron transport layer is too thick, it will introduce too much series resistance and affect the device efficiency.
[0026] Preferably, the thickness of the second electron transport layer is 20-40 nm, for example, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm, etc., preferably 25-30 nm.
[0027] Preferably, the solar cell assembly further comprises a conductive substrate, a hole transport layer, a perovskite absorption layer, the composite electron transport layer and an electrode; the light scattering layer in the composite electron transport layer is close to the perovskite absorption layer.
[0028] Preferably, the conductive substrate comprises conductive glass or conductive plastic. Exemplarily, the conductive glass may be, for example, FTO (fluorine-doped tin oxide) conductive glass or ITO (indium tin oxide) conductive glass, and the conductive plastic may be, for example, FTO (fluorine-doped tin oxide) conductive plastic or ITO (indium tin oxide) conductive plastic. In either the conductive glass or the conductive plastic, the thickness of the FTO layer may be 500 nm, and the thickness of the ITO layer may be 300-400 nm.
[0029] Preferably, the material of the hole transport layer includes nickel oxide and / or self-assembled small molecules.
[0030] Preferably, the general chemical formula of the perovskite absorption layer is ABX3, wherein A includes any one of methylamine ion, formamidine ion or cesium ion or a combination of at least two, B includes lead ion and / or tin ion, and X includes any one of chloride ion, bromide ion or iodide ion or a combination of at least two.
[0031] Preferably, the material of the electrode includes any one of Ag, Al, Au or TCO (transparent conductive oxide). Exemplarily, TCO may be ITO or FTO, for example.
[0032] Preferably, the thickness of the hole transport layer is 10-20 nm, for example, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm.
[0033] Preferably, the thickness of the perovskite absorption layer is 300-1000 nm, for example, 300 nm, 500 nm, 700 nm or 900 nm.
[0034] Preferably, the thickness of the composite electron transport layer is 30-60 nm, for example, 30 nm, 40 nm, 50 nm or 60 nm.
[0035] In the present invention, a composite electron transport layer of suitable thickness can form a good interface energy level arrangement in the battery component, promote the effective transmission of electrons from the perovskite layer to the electrode, help reduce the interface resistance, and improve the overall performance of the battery.
[0036] Preferably, the electrode has a layer thickness of 100-300 nm, for example, 100 nm, 200 nm or 300 nm.
[0037] In a second aspect, the present invention provides a method for preparing the composite electron transport layer as described in the first aspect, the preparation method comprising the following steps:
[0038] A substrate is provided, and a light scattering layer, a first electron transport layer and a second electron transport layer are stacked on the surface of the substrate to obtain the solar cell assembly.
[0039] Preferably, the substrate comprises a conductive substrate, a hole transport layer and a perovskite absorption layer which are stacked, and the light scattering layer is close to the perovskite absorption layer.
[0040] Preferably, the method for forming the light scattering layer comprises:
[0041] The nano-dispersion liquid is coated on a substrate, and the light scattering layer is obtained after annealing.
[0042] Preferably, the nano-dispersion liquid comprises an aluminum oxide nano-dispersion liquid and / or a silicon oxide nano-dispersion liquid.
[0043] Preferably, the concentration of the nano-dispersion liquid is 0.1-1 wt%, for example, it can be 0.1 wt%, 0.2 wt%, 0.25%, 0.5 wt%, 0.75 wt% or 1 wt%.
[0044] Preferably, the nano-dispersion liquid is further doped with a modified material, and the modified material includes a nitrogen-containing heterocyclic compound.
[0045] Preferably, in the nano-dispersion, the doping concentration of the modified material is 0.2-0.5 mg / mL, for example, 0.2 mg / mL, 0.3 mg / mL, 0.4 mg / mL or 0.5 mg / mL.
[0046] In the present invention, the modified material with a suitable doping concentration is helpful to improve the regular arrangement of the first electron transport layer and increase the electron transport rate of the composite electron transport layer.
[0047] Preferably, the method for forming the first electron transport layer includes any one of spin coating, spray coating or blade coating, or a combination of at least two of them.
[0048] Preferably, the second electron transport layer is formed by a thermal evaporation method.
[0049] Preferably, the preparation method comprises the following steps:
[0050] A hole transport layer and a perovskite absorption layer are sequentially formed on a conductive substrate.
[0051] A light scattering layer is formed on the perovskite absorption layer, and the specific steps include: coating a nano-dispersion liquid with a concentration of 0.1-1wt% on the perovskite absorption layer, and obtaining the light scattering layer after annealing; the nano-dispersion liquid is doped with a modified material, and the doping concentration of the modified material is 0.2-0.5mg / mL; wherein the nano-dispersion liquid includes an aluminum oxide nano-dispersion liquid and / or a silicon oxide nano-dispersion liquid, and the modified material includes a nitrogen-containing heterocyclic compound.
[0052] A first electron transport layer, a second electron transport layer and an electrode are sequentially formed on a surface of the light scattering layer away from the perovskite absorption layer to obtain a solar cell module.
[0053] Preferably, the preparation method of the conductive substrate includes a physical vapor deposition method, for example, evaporation or sputtering.
[0054] Preferably, the hole transport layer is formed by any one of a sputtering method, a spin coating method, a spray coating method or a blade coating method.
[0055] Preferably, the method for forming the perovskite absorption layer includes any one of an anti-solvent method, a vacuum method, a blowing method or a doctor blade method.
[0056] Preferably, the electrode is formed by vacuum evaporation or vacuum sputtering.
[0057] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] In the composite electron transport layer designed by the present invention, the light scattering layer can increase light scattering, improve the light absorption of perovskite, and improve the short-circuit current of the device. The first electron transport layer can not only fill the gaps formed by the agglomeration of nanoparticles in the light scattering layer and reduce the surface roughness, but also the first electron transport layer and the second electron transport layer with a conduction band price difference can accelerate electron transport and reduce carrier recombination. The three electron transport layers cooperate with each other to significantly improve the electron transport efficiency and stability of the composite electron transport layer, thereby obtaining device efficiency with excellent performance, and have good development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 This is a schematic diagram of the structure of the solar cell assembly provided in Example 1 of the present invention.
[0061] Figure 2 This is a schematic diagram of the energy levels of some functional layers in the solar cell module provided in Example 1 of the present invention.
[0062] Among them, 1-ITO conductive glass; 2-nickel oxide layer; 3-perovskite absorption layer; 41-light scattering layer; 42-first electron transport layer; 43-second electron transport layer; 4-composite electron transport layer; 5-electrode. DETAILED DESCRIPTION
[0063] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0064] Example 1
[0065] This embodiment provides a solar cell assembly, and its structural schematic diagram is as follows Figure 1 As shown, the solar cell assembly includes a stacked ITO conductive glass 1, a nickel oxide layer 2, a perovskite absorption layer 3, a composite electron transport layer 4 and an electrode 5; the composite electron transport layer 4 includes a light scattering layer 41, a first electron transport layer 42 and a second electron transport layer 43 stacked in sequence along a direction away from the perovskite absorption layer 3.
[0066] The thickness of the ITO layer in the ITO conductive glass 1 is 350 nm; the thickness of the nickel oxide layer 2 is 15 nm; the chemical formula of the perovskite absorption layer 3 is FA 0.9 Cs 0.1 PbI3, with a thickness of 600nm; the thickness of the composite electron transport layer 4 is 40nm, the material of the light scattering layer 41 is aluminum oxide particles, and the thickness of the light scattering layer 41 is 5nm; the material of the first electron transport layer 42 includes PCBM, the thickness of the first electron transport layer 42 is 5nm, and the first electron transport layer 42 is used to transport electrons and fill the gaps formed by the agglomeration of nanoparticles in the light scattering layer 41; the material of the second electron transport layer 43 includes C 60 The thickness of the second electron transport layer 43 is 30 nm, and there is a conduction band difference between the first electron transport layer 42 and the second electron transport layer 43; the electrode 5 is an Ag electrode with a thickness of 200 nm.
[0067] This embodiment also provides a method for preparing the above-mentioned solar cell assembly, and the preparation method comprises the following steps:
[0068] (1) A nickel oxide layer is deposited on the ITO conductive glass by magnetron sputtering, and then a perovskite absorption layer is prepared by the anti-solvent method.
[0069] (2) Spin coating an aluminum oxide nano-dispersion liquid with a concentration of 0.25 wt % on the perovskite absorption layer at 3000 rpm for 30 seconds. After the spin coating, annealing is performed at 100° C. for 10 minutes to remove the solvent, thereby forming a light scattering layer.
[0070] Wherein, the solvent of the aluminum oxide nano-dispersion liquid is isopropanol.
[0071] (3) A PCBM solution with a concentration of 5 mg / mL was spin-coated on the light scattering layer at 3000 rpm for 30 s. After the spin coating, the solution was annealed at 100° C. for 10 min to remove the solvent, thereby forming a first electron transport layer.
[0072] (4) Then, a layer of C is evaporated on the first electron transport layer by evaporation. 60 , forming the second electron transport layer, the evaporation rate is
[0073] (5) Then, a layer of Ag electrode is deposited by vacuum evaporation to obtain the solar cell module.
[0074] Figure 2 The schematic diagram of the energy levels of some functional layers in the solar cell module provided in this embodiment shows the energy level relationship between the perovskite absorption layer 3, the light scattering layer 41, the first electron transport layer 42 and the second electron transport layer 43. It can be seen from the figure that the light scattering layer 41 has a wide and thin band gap, and electrons can directly tunnel through it. The conduction band positions between the perovskite absorption layer 3, the first electron transport layer 42 and the second electron transport layer 43 are arranged in descending order, which can promote the effective transmission of electrons from the perovskite absorption layer 3 to the electrode.
[0075] Example 2
[0076] The present embodiment provides a solar cell assembly, which includes a stacked ITO conductive glass, a nickel oxide layer, a perovskite absorption layer, a composite electron transport layer and an electrode; the composite electron transport layer includes a light scattering layer, a first electron transport layer and a second electron transport layer which are stacked in sequence along a direction away from the perovskite absorption layer.
[0077] Among them, the thickness of the ITO layer in the ITO conductive glass is 350nm; the thickness of the nickel oxide layer is 15nm; the chemical formula of the perovskite absorption layer is FA 0.95 Cs 0.05 PbI3, with a thickness of 650nm; the thickness of the composite electron transport layer is 50nm, the material of the light scattering layer is silicon oxide particles, and the thickness of the light scattering layer is 10nm; the material of the first electron transport layer is PCBM, the thickness of the first electron transport layer is 5nm, and the first electron transport layer is used to transport electrons and fill the gaps formed by the agglomeration of nanoparticles in the light scattering layer; the material of the second electron transport layer is C 60 The thickness of the second electron transport layer is 35 nm, and there is a conduction band difference between the first electron transport layer and the second electron transport layer; the electrode is an Ag electrode with a thickness of 200 nm.
[0078] This embodiment also provides a method for preparing the above-mentioned solar cell assembly, and the preparation method comprises the following steps:
[0079] (1) A nickel oxide layer is deposited on the ITO conductive glass by magnetron sputtering, and then a perovskite absorption layer is prepared by the anti-solvent method.
[0080] (2) Spin coating a 0.5 wt % silicon oxide nano-dispersion liquid on the perovskite absorption layer at 3000 rpm for 30 seconds. After the spin coating, annealing was performed at 100° C. for 10 minutes to remove the solvent, thereby forming a light scattering layer.
[0081] Wherein, the solvent of the silicon oxide nano-dispersion liquid is isopropanol.
[0082] (3) Then, a PCBM solution with a concentration of 5 mg / mL was spin-coated on the light scattering layer at 3000 rpm for 30 s. After the spin coating, the solution was annealed at 100° C. for 10 min to remove the solvent, thereby forming a first electron transport layer.
[0083] (4) Then, a layer of C is evaporated on the first electron transport layer by evaporation. 60 , forming the second electron transport layer, the evaporation rate is
[0084] (5) Then, a layer of Ag electrode is deposited by vacuum evaporation to obtain the solar cell module.
[0085] Example 3
[0086] The present embodiment provides a solar cell assembly, which includes a stacked ITO conductive glass, a nickel oxide layer, a perovskite absorption layer, a composite electron transport layer and an electrode; the composite electron transport layer includes a light scattering layer, a first electron transport layer and a second electron transport layer which are stacked in sequence along a direction away from the perovskite absorption layer.
[0087] Among them, the thickness of the ITO layer in the ITO conductive glass is 350nm; the thickness of the nickel oxide layer is 15nm; the chemical formula of the perovskite absorption layer is MAPbI3, and the thickness is 600nm; the thickness of the composite electron transport layer is 48nm; the material of the light scattering layer is aluminum oxide particles, and the thickness of the light scattering layer is 3nm; the material of the first electron transport layer is PCBM, and the thickness of the first electron transport layer is 5nm. The first electron transport layer is used to transport electrons and fill the gaps formed by the agglomeration of nanoparticles in the light scattering layer; the material of the second electron transport layer is C 60 The thickness of the second electron transport layer is 40 nm, and there is a conduction band difference between the first electron transport layer and the second electron transport layer; the electrode is an Ag electrode with a thickness of 200 nm.
[0088] This embodiment also provides a method for preparing the above-mentioned solar cell assembly, and the preparation method comprises the following steps:
[0089] (1) A nickel oxide layer is deposited on the ITO conductive glass by magnetron sputtering, and then a perovskite absorption layer is prepared by the anti-solvent method.
[0090] (2) Spin coating an aluminum oxide nano-dispersion liquid with a concentration of 0.25 wt % on the perovskite absorption layer at 5000 rpm for 30 seconds. After the spin coating, annealing is performed at 100° C. for 10 minutes to remove the solvent, thereby forming a light scattering layer.
[0091] Wherein, the solvent of the aluminum oxide nano-dispersion liquid is isopropanol.
[0092] (3) Then, a PCBM solution with a concentration of 5 mg / mL was spin-coated on the light scattering layer at 3000 rpm for 30 s. After the spin coating, the solution was annealed at 100° C. for 10 min to remove the solvent, thereby forming a first electron transport layer.
[0093] (4) Then, a layer of C is evaporated on the first electron transport layer by evaporation. 60 , forming the second electron transport layer, the evaporation rate is
[0094] (5) Then, a layer of Ag electrode is deposited by vacuum evaporation to obtain the solar cell module.
[0095] Example 4
[0096] The difference between this embodiment and embodiment 1 is that the material of the light scattering layer includes aluminum oxide particles and 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole, and the doping concentration of 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole in the aluminum oxide nano-dispersion is 0.2 mg / mL, that is, 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole is introduced into the aluminum oxide nano-dispersion in step (2).
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Example 5
[0099] The difference between this embodiment and embodiment 1 is that the thickness of the light scattering layer is 0.5 nm by adjusting the spin coating rate of the aluminum oxide nano-dispersion liquid in step (2).
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Example 6
[0102] The difference between this embodiment and embodiment 1 is that the thickness of the light scattering layer is 20 nm by adjusting the spin coating rate of the aluminum oxide nano-dispersion liquid in step (2).
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 7
[0105] The difference between this embodiment and embodiment 1 is that the thickness of the first electron transport layer is 0.5 nm by adjusting the spin coating rate of the PCBM solution in step (3).
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 8
[0108] The difference between this embodiment and embodiment 1 is that the thickness of the first electron transport layer is 20 nm by adjusting the spin coating rate of the PCBM solution in step (3).
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Comparative Example 1
[0111] The difference between this comparative example and Example 1 is that no light scattering layer is provided, that is, step (2) is not performed.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 1 is that the first electron transport layer is not provided, that is, step (3) is not performed.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Comparative Example 3
[0117] The difference between this comparative example and Example 1 is that no second electron transport layer is provided, that is, step (4) is not performed.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Comparative Example 4
[0120] The difference between this comparative example and Example 1 is that the composite electron transport layer includes a light scattering layer, a second electron transport layer and a first electron transport layer which are stacked, that is, after step (2), step (4) is performed first, and then step (3) is performed.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Performance Testing
[0123] The photovoltaic performance of the solar cell modules provided in the above embodiments and comparative examples was tested under the following conditions: the test area was 1 cm 2 , AM1.5, 1000W / m 2 , 25±2℃.
[0124] The test results are shown in Table 1.
[0125] Table 1
[0126]
[0127] analyze:
[0128] It can be seen from the above table that in the composite electron transport layer designed by the present invention, the light scattering layer can increase light scattering, improve perovskite absorption, and increase the short-circuit current of the device. The first electron transport layer can not only fill the gaps formed by the agglomeration of nanoparticles in the light scattering layer and reduce the surface roughness, but also the first electron transport layer and the second electron transport layer with a conduction band price difference can accelerate electron transport and reduce carrier recombination. The three electron transport layers work together to significantly improve the electron transport efficiency and stability of the composite electron transport layer, thereby obtaining device efficiency with excellent performance.
[0129] It can be seen from Examples 1 and 4 that if 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole is introduced into the light scattering layer, it is helpful to help the regular arrangement of PCBM in the subsequent first electron transport layer and enhance the electron transport capacity.
[0130] It can be seen from Examples 1 and 5-6 that if the light scattering layer is too thin, it will not play a role in light scattering, resulting in poor device performance; if the light scattering layer is too thick, it will affect electron transmission due to poor conductivity, resulting in poor device performance.
[0131] It can be seen from Example 1 and Examples 7-8 that if the thickness of the first electron transport layer is too thin, it will not be able to fill the gaps in the light scattering layer, alleviate the unevenness of the upper surface, and reduce the surface roughness, resulting in a decrease in the efficiency of the manufactured device; if the thickness of the first electron transport layer is too thick, it will introduce too much series resistance, affecting the device efficiency.
[0132] It can be seen from Example 1 and Comparative Example 1 that if the light scattering layer is not provided, part of the light scattering will be lost, resulting in a decrease in the device current.
[0133] It can be seen from Example 1 and Comparative Example 2 that if the first electron transport layer is not provided, the interface electron transport will be affected, resulting in a significant decrease in the fill factor of the device.
[0134] It can be seen from Example 1 and Comparative Example 3 that if the second electron transport layer is not provided, the electron transport capacity decreases, resulting in a significant decrease in the fill factor and efficiency of the device.
[0135] It can be seen from Example 1 and Comparative Example 4 that if the composite electron transport layer includes a stacked light scattering layer, a second electron transport layer and a first electron transport layer, the electrons will not be able to be quickly separated from the perovskite layer and injected into the electrode layer, and will severely recombine with the holes, resulting in a serious decrease in device efficiency.
[0136] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A solar cell module having a composite electron transport layer, characterized in that: The composite electron transport layer comprises a light scattering layer, a first electron transport layer and a second electron transport layer which are stacked: The light scattering layer is used to absorb the first light and form scattering; the first electron transport layer is used to transport electrons and fill the gaps in the light scattering layer; and there is a conduction band difference between the first electron transport layer and the second electron transport layer.
2. The solar cell assembly according to claim 1, characterized in that: The material of the light scattering layer includes nano oxide particles; Preferably, the nano oxide particles include aluminum oxide and / or silicon oxide; Preferably, the material of the light scattering layer further comprises a nitrogen-containing heterocyclic compound; Preferably, the nitrogen-containing heterocyclic compound includes 1,3-dimethyl-2-phenyl-2,3-dihydro-1H-benzo[d]imidazole.
3. The solar cell assembly according to claim 1 or 2, characterized in that: The thickness of the light scattering layer is 1-10 nm, preferably 5-10 nm.
4. The solar cell assembly according to any one of claims 1 to 3, characterized in that: The material of the first electron transport layer includes a fullerene derivative; Preferably, the fullerene derivatives include [6,6]-phenyl-C61-butyric acid methyl ester and / or indene-C 60 Bisadducts; Preferably, the material of the second electron transport layer includes C 60 .
5. The solar cell assembly according to any one of claims 1 to 4, characterized in that: The thickness of the first electron transport layer is 1-10 nm, preferably 5-10 nm; Preferably, the thickness of the second electron transport layer is 20-40 nm, preferably 25-30 nm.
6. The solar cell assembly according to any one of claims 1 to 5, characterized in that: The solar cell assembly further comprises a conductive substrate, a hole transport layer, a perovskite absorption layer, the composite electron transport layer and an electrode; the light scattering layer in the composite electron transport layer is close to the perovskite absorption layer; Preferably, the conductive substrate comprises conductive glass or conductive plastic; Preferably, the material of the hole transport layer includes nickel oxide and / or self-assembled small molecules; Preferably, the chemical formula of the perovskite absorption layer is ABX3, wherein A includes any one of methylamine ion, formamidine ion or cesium ion or a combination of at least two thereof, B includes lead ion and / or tin ion, and X includes any one of chloride ion, bromide ion or iodide ion or a combination of at least two thereof; Preferably, the material of the electrode includes any one of Ag, Al, Au or TCO.
7. The solar cell assembly according to claim 6, characterized in that: The thickness of the hole transport layer is 10-20 nm; Preferably, the thickness of the perovskite absorption layer is 300-1000 nm; Preferably, the thickness of the composite electron transport layer is 30-60 nm; Preferably, the electrode has a layer thickness of 100-300 nm.
8. A method for preparing a solar cell module according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: A substrate is provided, and a light scattering layer, a first electron transport layer and a second electron transport layer are stacked on the surface of the substrate to obtain the solar cell assembly.
9. The preparation method according to claim 8, characterized in that: The substrate comprises a conductive substrate, a hole transport layer and a perovskite absorption layer which are stacked, and the light scattering layer is close to the perovskite absorption layer; Preferably, the method for forming the light scattering layer comprises: coating the nano-dispersion on the substrate and annealing to obtain the light scattering layer; Preferably, the deposition method of the first electron transport layer includes any one of spin coating, spray coating or blade coating, or a combination of at least two thereof; Preferably, the deposition method of the second electron transport layer includes thermal evaporation.
10. The preparation method according to claim 8 or 9, characterized in that: The preparation method comprises the following steps: forming a hole transport layer and a perovskite absorption layer in sequence on a conductive substrate; A light scattering layer is formed on the perovskite absorption layer, and the specific steps include: coating a nano-dispersion liquid with a concentration of 0.1-1wt% on the perovskite absorption layer, and obtaining the light scattering layer after annealing; the nano-dispersion liquid is doped with a modified material, and the doping concentration of the modified material is 0.2-0.5mg / mL; wherein the nano-dispersion liquid includes an aluminum oxide nano-dispersion liquid and / or a silicon oxide nano-dispersion liquid, and the modified material includes a nitrogen-containing heterocyclic compound; A first electron transport layer, a second electron transport layer and an electrode are sequentially formed on a surface of the light scattering layer away from the perovskite absorption layer to obtain a solar cell module.
Citation Information
Cited By
Solar cell module and preparation method therefor
WO2026124476A1